Pengaruh Brand Trust dan Kualitas Produk Terhadap Keputusan Pembelian Laptop Axioo pada Mahasiswa di Kota Palembang - Achmad Anjas Asmara; Aslamia Rosa; Yulia Hamdaini Putri (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The Influence of Brand Trust and Product Quality on the Purchase Decision of Axioo Laptops in Palembang City This study aims to analyze the influence of brand trust and product quality on the purchase decision of Axioo laptops in Palembang City. The research employs a quantitative approach using primary data obtained through questionnaires. The independent variables in this study are brand trust (X1) and product quality (X2), while the dependent variable is the purchase decision (Y). The analysis results indicate that partially, both brand trust (X1) and product quality (X2) have a positive influence on the purchase decision. Additionally, simultaneously, these independent variables also have a positive influence on the purchase decision of Axioo laptops. These findings suggest that consumers' trust in the brand and good product quality play a crucial role in driving purchase decisions. Therefore, it is recommended that the company continues to enhance consumers' trust in the brand and maintain product quality to strengthen its competitiveness in the market.